Energy Conservation Approach for Continuous Power Quality Improvement: A Case Study - Lalith Pankaj Raj Nadimuthu (IEEE, 2021)
This work focused on a harmonic mitigating filter and investigated the effect of the harmonic mitigating filter in the textile industry with innovative energy conservation strategies for energy bill reduction, which covers a pathway to climate change mitigation. Here, the effect of the harmonic filter is found out by the systematic energy audit methodology (Preliminary, Detailed and Post-Audit phase). From the energy auditing, it has been found that the textile industry needed a passive harmonic filter for harmonic mitigation. Since, third, fifth, and seventh order of harmonic predominantly exists in the system. The high stability at higher current, known tuning frequency, low cost and low power consumption makes the passive filter to be the best fit for the system. The voltage and current Total Harmonic Distortion Factor (THDF) have been measured using the class ‘A’ power quality and energy analyzer. The harmonic filter’s effect in harmonics mitigation is prominent; 66.45% of the reduction of current harmonics which is achieved after installing the passive filter at the Point of Common Coupling (PCC) of the system. Also, the reduction of harmonics ensures energy conservation through the reduction of additional losses (joule, copper and eddy current losses). The techno-economic analysis with payback period calculation is carried out and reported. Also, the effect of harmonics like mechanical anomalies (temperature rise) is carefully studied using an infrared thermo graphic technique in the textile industry’s motor loads. The energy conservation and their carbon emission reduction are calculated and reported.